Enhancing the Students’ Pronunciation Using Shadowing Technique at Senior High School Students - Salim, Agus; Terasne, Terasne; Narasima, Liza (JOLLT Journal of Languages and Language Teaching, 2020)
Establishing students’ pronunciation needs a promising instructional method. One of the teachers’ efforts to develop students’ pronunciation is applying the shadowing technique. The shadowing technique was able to facilitate students to practice pronunciation skills. This study was categorized with a quasi-experimental study with the non-equivalent control group design. The samples were taken randomly using a purposive random sampling. The samples consist of 70 students that were divided into two classes, namely the experimental and control classes. The data were collected through interview, multiple-choice test, and record. Here it used descriptive and T-test analysis to find the ways they learned and the results. Finally, the researchers considered that shadowing technique is very good to be applied by the teachers and lecturers in class. The most surprising aspect of the findings are; 1) the students were motivated as long as teaching and learning conducted; 2) their response mostly positive to the way they learned; 3) and they got significant change on their pronunciation, grammar and vocabulary. This change can be seen from their ability in expressing their ideas and 4) inferential statistic results; t-test was 4.077 and t-table was 2.021 with degree of freedom (df) 44 and the level of significance (0.05) in 95%.